MENGEMAS KEBOSANAN DALAM RUMAH TANGGA - Rochman, Kholil Lur (Fakultas Dakwah IAIN Purwokerto, 2012)
Marital life is a form of cooperation between a husband and a wife whichsometimes experiences disharmony. There are always ups and downs in it, and both of thewife and husband need to show their maturity to resolve all the problems that may arise atany time. However, sometimes the couple cannot build good cooperation in solving aproblem or even tend to worsen the situation. Such a situation can create an unhealthymarital life.If such a condition is ignored, it would be worse. A feeling of boredom andannoyed will potentially occurred in their relationship. Boredom is closely related to thepurpose of life. The more clear and meaningful purpose in life, the easier it is to overcomeboredom. Conversely, without a clear purpose and meaningful life, it will be more difficultto overcome it. In running their life, families have to refer to their purpose of life byorganizing and planning activities to achieve their goals in life.